Prototype of Electric Power Monitoring System and Load Control in Residential Houses Using IoT-Based ESP8266 - Dika Herdika; Endah Fitriani (Jurnal Ampere, 2022)
The use of the Internet of Think (IoT) for a system that can monitor the use of load and electrical power in a residential house will be very necessary. This is because homeowners who often go out and leave their homes with loads that are still active, for example, house lights that are always turned on will be a waste of electrical energy. The purpose of making this article is to create a system that can control electricity use automatically using the Internet Of Think (IoT) and monitor the electricity data in real time, calculate the amount of current, voltage, and power in an entire load. Calculating the comparison of sensor and manual values by looking at the percentage of errors on the sensor, and analyzing whether the sensor is suitable for use or not. The systems used are: Pzem 004t as an overall reader of electrical power, LDR sensor as light input to turn on the lights automatically when it is dark, and nodemcu esp8266 as input/output process and sends data to the internet via a wifi network which will be monitored through the application. Blynk Iot 2.0 ABSTRAKPenggunaan Internet of Think (IoT) untuk sistem yang dapat memonitoring penggunaan beban dan daya listrik pada sebuah rumah tinggal akan sangat diperlukan. Hal tersebut karena pemilik rumah yang sering berpergian keluar dan meninggalkan rumahnya dengan beban yang masih aktif contohnya lampu rumah yang selalu dihidupkan akan menjadi pemborosan energi listrik tersebut. Tujuan dari pembuatan artikel ini adalah yaitu membuat sistem yang dapat mengontrol penggunaan listrik secara otomatis menggunakan Internet Of Think (IoT) serta memonitoring data listrik tersebut secara realtime, menghitung jumlah arus, tegangan, dan daya pada suatu keseluruhan beban yang ada. Menghitung perbandingan nilai sensor dan manual dengan cara melihat persentase kesalahan pada sensor tersebut, dan menganalisa pada sensor tersebut layak digunakan atau tidak. Adapun sistem yang digunakan yaitu: Pzem 004t sebagai pembaca keseluruhan daya listrik, sensor LDR sebagai input cahaya untuk menghidupkan lampu secara otomatis ketika hari sudah gelap, dan nodemcu esp8266 sebagai proses input/ouput dan pengirim data ke internet melalui jaringan wifi yang akan dimonitoring lewat aplikasi Blynk Iot 2.0.